ASSESSING COGNITIVE AUTONOMY ACROSS DIVERSE LEARNER POPULATIONS: DEVELOPMENT AND VALIDATION OF A NOVEL COGNITIVE AUTONOMY ASSESSMENT DEVICE - S. KUMARAN ARUL DEVARAM,; Dr.S.GUNASEKARAN, (The Bioscan, 2026)
Cognitive autonomy is a crucial component of effective learning, enabling individuals to think independently, make informed decisions, regulate their learning processes, and adapt to diverse educational environments. Despite its importance, there is a lack of inclusive and empirically validated instruments capable of assessing cognitive autonomy across heterogeneous learner populations. This study reports the development and validation of a novel Cognitive Autonomy Assessment Device designed to measure key dimensions of cognitive autonomy among learners from diverse cultural, linguistic, socioeconomic, and educational backgrounds. The device was developed through a systematic multi-phase process involving construct identification, expert review, item generation, pilot testing, and large-scale validation. Data were collected from a diverse sample of undergraduate students representing rural and urban settings, multilingual communities, and first-generation learners. Statistical analyses, including content validity assessment, reliability testing, exploratory factor analysis, and confirmatory factor analysis, were employed to establish the psychometric properties of the instrument. The findings demonstrated strong reliability, satisfactory construct validity, and robust measurement invariance across learner groups. The study further revealed significant associations between cognitive autonomy and academic engagement, self-regulated learning, and critical thinking skills. The proposed assessment device offers educators, researchers, and policymakers a reliable tool for promoting inclusive educational practices and understanding learner diversity in contemporary higher education contexts.